The utilisation of services by patients with psychosis who engage in antisocial behaviours. Issue 1 (2nd January 2023) - Challinor, Alexander; Whyler, Jonathon; Meggison, Neil; Cresswell, Phoebe; Evans, Leah; Bingley, Michael; Somarathne, Praveen; Thompson, Jodi; McIntyre, Jason; Washington, Dawn; Nathan, Rajan
ABSTRACT: Three pathways of antisocial behaviour and psychosis have been described. Three subgroups within a typology have been categorised as (i) schizophrenia preceded by conduct disorder (SZ+CD), (ii) offenders with schizophrenia and no childhood history of antisocial behaviour who begin offending at illness onset (SZ+AS), and (iii) offenders with schizophrenia (SZ). There are no studies investigating how the subgroups utilise services. This study aimed to examine the concurrent validity of typology and examine differences in service utilisation. The sample consisted of 77 male patients admitted to low- and medium-secure units in the United Kingdom. The subgroup of patients was determined from data collected from health records. Analysis assessed the difference in aetiological variables amongst the typology and examined the relationship of subgroup service utilisation. This study provided further evidence of distinguishing characteristics emphasising typology heterogeneity and found differences in service utilisation. The SZ+CD subgroup was more likely to have used services preceding a diagnosis of psychosis. Following the onset of psychosis, the SZ+AS and SZ subgroups had a higher proportion that used general adult psychiatry services. Those patients within the SZ+AS and SZ subgroups had a higher use of general adult services after psychosis onset. Understanding about how these subgroups utilise services will enable clinicians to develop effective management plans that address the distinct characteristics of offenders with psychosis.